2022
DOI: 10.1111/jam.15458
|View full text |Cite
|
Sign up to set email alerts
|

The major component of cinnamon oil as a natural substitute against Fusarium solani on Astragalus membranaceus

Abstract: Aims: Root rot caused by Fusarium solani is an important disease seriously affecting the yield and quality of Astragalus membranaceus. Therefore, this study was performed to elucidate the antifungal activities and mechanisms of cinnamaldehyde treatment against F. solani and its control effect for A. membranaceus root rot. Methods and Results: Cinnamaldehyde significantly inhibited mycelial growth and spore germination of F. solani in dose-dependent, and the median effective concentration was 178.68 μl l −1 . F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 58 publications
1
8
0
Order By: Relevance
“…Similar results were also observed for the mechanism of action of cinnamon oil, containing 92.4% of cinnamaldehyde, against the bacteria Escherichia coli and Staphylococcus aureus, in which cinnamon oil in effective concentrations (2.0 and 4.0 mg ml −1 ) affects cell membrane integrity, permeability and structures, and also irregular cell metabolic activity (Zhang et al, 2016). Wang et al (2022) also studied the fungicide effect of cinnamon oil and its major component, the cinnamaldehyde, and showed that cinnamaldehyde was effective to inhibit mycelial growth and spore germination of Fusarium solani at a concentration of 178.68 μl L −1 .…”
Section: Alternaria Alternata Fusarium Fol27supporting
confidence: 73%
See 2 more Smart Citations
“…Similar results were also observed for the mechanism of action of cinnamon oil, containing 92.4% of cinnamaldehyde, against the bacteria Escherichia coli and Staphylococcus aureus, in which cinnamon oil in effective concentrations (2.0 and 4.0 mg ml −1 ) affects cell membrane integrity, permeability and structures, and also irregular cell metabolic activity (Zhang et al, 2016). Wang et al (2022) also studied the fungicide effect of cinnamon oil and its major component, the cinnamaldehyde, and showed that cinnamaldehyde was effective to inhibit mycelial growth and spore germination of Fusarium solani at a concentration of 178.68 μl L −1 .…”
Section: Alternaria Alternata Fusarium Fol27supporting
confidence: 73%
“…Cinnamaldehyde, the main component of cinnamon oil, had strong effects in Fusarium solani and cause changes of the mycelial morphology, plasma membrane damages and blocked the biosynthesis of ergosterol (Wang et al, 2022). Similar results were also observed for the mechanism of action of cinnamon oil, containing 92.4% of cinnamaldehyde, against the bacteria Escherichia coli and Staphylococcus aureus , in which cinnamon oil in effective concentrations (2.0 and 4.0 mg ml −1 ) affects cell membrane integrity, permeability and structures, and also irregular cell metabolic activity (Zhang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nox (NADPH oxidase) is an important enzyme generating ROS in eukaryotes [ 45 ]. Nox-produced ROS contributes to the cell leakage in fungi [ 46 ]. Besides damaging the cell membrane, ROS can act on mitochondrial proteins to induce fungal death [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Park [21] explained the antifungal activity of eugenol compounds from clove oil against Trichophyton mentagrophytes showed that eugenol compounds cause abnormal mitochondrial structure, partial damage to the mitochondrial core membrane and complete damage to the hyphal cell wall. Meanwhile, cinnamaldehyde from cinnamon oil could alter the mycelial morphology, damage the plasma membrane and hinder the biosynthesis of ergosterol of A. membranaceus [22]. Scanning electron microscopy results on Fusarium verticillioid showed that cinnamaldehyde damaged cytoplasmic contents, cell wall integrity and rigidity and destroyed mitochondria and cell folding [23].…”
Section: In Vitro Effects Of Clove and Cinnamon Oil On Mycelial Growthmentioning
confidence: 99%